Perancangan Lukisan Augmented Reality Dalam Meningkatkan Kesadaran Masyarakat Terhadap Kerusakan Ekosistem Laut - Hironimus, Tulus Jethro; Noviana, Eka (Cipta, 2025)
Marine debris is a severe environmental problem in Indonesia. Plastic waste and other waste that pollute the oceans harm the ecosystem and endanger human health. Raising public awareness of this problem requires an effective and engaging approach. One possible solution is using augmented reality (AR) technology in interactive art exhibitions. The purpose of this study is to develop an AR-based interactive art exhibition that can increase public understanding and awareness of the impacts of marine debris. Through digital illustrations, AR animations, and even collaboration with renowned artist Red Miller Blood, exhibition visitors are directly involved in understanding the problem and finding creative solutions.